Evaluating Midwifery Units (EMU): a prospective cohort study of freestanding midwifery units in New South Wales, Australia. Issue 10 (31st October 2014) - Monk, Amy; Tracy, Mark; Foureur, Maralyn; Grigg, Celia; Tracy, Sally
Abstract : Objective: To compare maternal and neonatal birth outcomes and morbidities associated with the intention to give birth in two freestanding midwifery units and two tertiary-level maternity units in New South Wales, Australia. Design: Prospective cohort study. Participants: 494 women who intended to give birth at freestanding midwifery units and 3157 women who intended to give birth at tertiary-level maternity units. Participants had low risk, singleton pregnancies and were at less than 28 +0 weeks gestation at the time of booking. Primary and secondary outcome measures: Primary outcomes were mode of birth, Apgar score of less than 7 at 5 min and admission to the neonatal intensive care unit or special care nursery. Secondary outcomes were onset of labour, analgesia, blood loss, management of third stage of labour, perineal trauma, transfer, neonatal resuscitation, breastfeeding, gestational age at birth, birth weight, severe morbidity and mortality. Results: Women who planned to give birth at a freestanding midwifery unit were significantly more likely to have a spontaneous vaginal birth (AOR 1.57; 95% CI 1.20 to 2.06) and significantly less likely to have a caesarean section (AOR 0.65; 95% CI 0.48 to 0.88). There was no significant difference in the AOR of 5 min Apgar scores, however, babies from the freestanding midwifery unit group were significantly less likely to be admitted to neonatal intensive care or special care nursery (AOR 0.60; 95% CI 0.39 to 0.91). Analysis of secondary outcomes indicated that planning to give birth in a freestanding midwifery unit was associated with similar or reduced odds of intrapartum interventions and similar or improved odds of indicators of neonatal well-being. Conclusions: The results of this study support the provision of care in freestanding midwifery units as an alternative to tertiary-level maternity units for women with low risk pregnancies at the time of booking.